Rethinking and Reconnecting Urban River Corridor: Studi Kasus DAS Garang, Semarang - Yohana Aneke; Cornelius Gea (Archvisual: Jurnal Arsitektur dan Perencanaan, 2022)
Urban river corridors have an important role in the development of cities. Since early civilizations rivers have served as navigation, irrigation, domestic and industrial water supply, defense, and energy production. In general, rivers have hydrological and ecological functions as a buffer for the natural balance. The relationship between upstream, middle, and downstream has causal connectivity that will affect each other. The river that passes through the city space will cause problems if it is not managed properly. But, engineering projects on the natural dynamics of rivers have now reached a critical point. This research uses qualitative research methods, through observing phenomena in the field, collecting primary data and secondary data to produce new findings. This research found that various pressures from climate change, spatial changes, and the increasing number of flood events have made all these efforts to solve river problem need to be rethought. Various government projects such as flood prevention and river normalization projects continue to this day. However, it has not been able to fully respond to river problems. Thus, there is a need for a strategy to initiate the transition to a more resilient and sustainable approach.